Estudo teórico e experimental dos espectros de absorção uv/vis e algumas propriedades moleculares da bergenina - Diego dos Santos, Freitas (2013)
Bergenin is an isocoumarin typically found in tropical forest species, such as the Amazonian species Uchi-amarelo (Endopleura uchi), in which the substance is distributed in its leaves, bark and fruits. The literature reports several biological activities for bergenin, among which we mention the following main activities: antioxidant, hepatoprotective, anti-inflammatory and antiulcer. In this work, the spectra UV / Visible bergenin of water and ethanol were studied by UV spectroscopy and computational methods. Were calculated excitation energies, oscillator strength using the Density Functional Theory of Time-Dependent (TD-DFT) using the B3LYP functional and the basis set 6-31G*. Furthermore, the effect of solvent on the molecule has been discussed based on the HF/6-31G* ab initio calculations performed to determine the molecular structure and properties of some molecules. The computational studies for the molecule showed that the chemical structure of bergenin is not planar, with a kind chair conformation in ring D-glucopyranose to - 148.99° out of the plane, the dipole moment of 0,94D, the energy gap (εgap) of 11.14 and logP of -1.40. The UV / Vis simulated were compatible with the experimental spectra. After the computations molecule simulating the ethanol solvent and water separately, it was observed that the structural conformation of bergenin not suffer large variations, however, its dipole moment changed to 2.80D and 1.33D, respectively, as well as gap energy to 11eV and 10.97eV. There was no change in logP during the study the effect of solvent. The results indicated that bergenin interacts with more ethanol than water, however, the solvent used for the simulation did not alter the lipophilicity of the molecule. In addition, results using the computational methods obtivos, after comparison with the results obtained by experimental methods in this study and the results reported in the literature were compatible, indicating that the photoactive region or chromophoric molecule is localized on the phenyl ring, this being the region that contributes to the biological activity of bergenin.